Determination of the total content of some secondary metabolites in various organs of the Dagestan samples of Capparis herbacea Willd. - F. A. Vagabova; G. K. Radjabov; A. M. Musaev; F. I. Islamova (Овощи России, 2021)
Relevance, material and methods. Purpose of the work: comparative assessment of the content of the sum of phenolic compounds exhibiting antioxidant activity in various organs of herbaceous capers C. herbacea Willd. The 4 samples of C. herbaceawere collected from natural populations of Dagestan during the flowering and fruiting phases in the summer of 2019. The collected raw materials were divided into fractions (organs), dried in the shade to an air-dry mass, then subjected to further analysis to determine the total content of flavonoids, anthocyanins by the spertrophotometric method on SF-56; the total content of antioxidants by the amperometric method on the instrument of express analysis "Color-Yauza-001-AAA ".Results. During the analysis, good indicators were obtained for the content of the studied compounds. Thus, in terms of the content of flavonoids, the greatest variation is seen in the stems of herbaceous capers (0.34-0.86%) compared to their content in leaves and inflorescences (2.67-2.97% and 2.45-2.90%, respectively). The amount of anthocyanins varies in all organs within the range of 0.05-0.23%. The smallest spread is observed in the total content of antioxidants in the fruits of herbaceous capers (21.35-21.40 mg/l), while in inflorescences this indicator varies greatly (27.44-42.19 mg/l). It is noteworthy that the samples with a high value of antioxidants showed a low content of flavonoids, thereby indicating that flavonoids are not the main components in the antioxidant system of the studied caper species. An important condition determining the variability of the content of phenolic compounds in various plant organs is a complex of abiotic environmental factors. The study of this factor (altitude gradient) revealed a significant relationship with the accumulation of flavonoids in all organs, which has a multi-vector nature (correlation coefficient r*= 0.57; 0.56; -0.47), respectively, in stems, leaves, and inflorescences (P<0,05). A positive relationship in the accumulation of anthocyanins is observed with the height in caper leaves. In all other cases, the connection is random. In addition, the analysis of variance revealed that a large difference in the variability of the studied compounds is observed between individual groups of plants in the absence of intragroup variability.